Cochlea cell-specific marker expression upon in vitro Hes1 knockdown - Batissoco,A.C. (2021)
NOTCH pathway proteins, including the transcriptional factor HES1, play crucial roles in the development of the inner ear by means of the lateral inhibition mechanism, in which supporting cells have their phenotype preserved while they are prevented from becoming hair cells. Genetic manipulation of this pathway has been demonstrated to increase hair cell number. The present study aimed to investigate gene expression effects in hair cells and supporting cells after Hes1-shRNA lentivirus transduction in organotypic cultures of the organ of Corti from postnatal-day-3 mice. Forty-eight hours after in vitro knockdown, Hes1 gene expression was reduced at both mRNA and protein levels. Myo7a (hair cell marker) and Sox2 (progenitor cell marker) mRNA levels also significantly increased. The modulation of gene expression in the organ of Corti upon Hes1 knockdown is consistent with cell phenotypes related to lateral inhibition mechanism interference in the inner ear. The lentivirus-based expression of Hes1-shRNA is a valuable strategy for genetic interference in the organ of Corti and for future evaluation of its efficacy in protocols aiming at the regeneration of hair cells in vivo.